2006
DOI: 10.1097/01.tp.0000232693.69773.42
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Living Kidney Donation: Is There a Lack of Willing Donors or an Excess of Medically Unsuitable Candidates?

Abstract: Determining the reason behind nondonation is a first step towards understanding low rates of live kidney donation. More African American donor referrals are lost to follow-up while rates of other reasons were similar among races. This may indicate that African Americans are not more frequently medically unsuitable, but that the divergence in rates of live kidney donation is caused by a disparity in willingness to donate among African Americans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
96
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(105 citation statements)
references
References 27 publications
6
96
2
1
Order By: Relevance
“…Many candidates did not receive LDKTs because their recruited donors lacked further interest in living donation. Potential living donors who are black are more likely to be lost to follow-up and lose interest in living donation (12,13). Thus, efforts to decrease donor "dropout" may especially increase donor conversion and LDKT among black transplant candidates.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many candidates did not receive LDKTs because their recruited donors lacked further interest in living donation. Potential living donors who are black are more likely to be lost to follow-up and lose interest in living donation (12,13). Thus, efforts to decrease donor "dropout" may especially increase donor conversion and LDKT among black transplant candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies could not examine these steps because they examined transplant candidates but lacked data on candidates' potential living donors (2,4,7), examined recipients of LDKTs but lacked data on candidates who did not receive LDKTs (2,7-9,35), or examined potential living donors but lacked data on donors' intended recipients (11)(12)(13)36). Several recent studies have reported reasons for nondonation by recruited, potential living donors (11)(12)(13)36). Although informative, these donor-based studies lacked information about donors' associated transplant candidates, preventing examination of donor recruitment and conversion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations